Tension Management in the Process of Sustainable Development: Take Stated-owned Enterprises as an Example - Chen, Da (2020)
Sustainable development is the ultimate development goal pursued by humankind, but it requires the simultaneous advancement of the economy, society and the environment, individuals or organizations need to achieve mutually competing sustainable development goals at the same time, which creates tension. Although recent work has provided a specific theoretical basis for this tension, it is entirely insufficient, and empirical research is even more lacking. Existing cases are also related to private or international enterprises, there is no literature focus on the tensions in state-owned enterprises. In this case, the researchers interviewed 21 employees from Chinese state-owned enterprises.The researcher also analyzed the central tensions and the effective tension strategies in it and the underlying logic of the coexistence of paradox and synergy in the tension theory. These works explain the existing theories and put forward the view that more detailed research is needed for different enterprise properties and actual environments in the future, which will help individuals or organizations to manage tension better.